Dampak Beban Kerja, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai (Studi Kasus pada Biro Organisasi Setda Provinsi Sulawesi Selatan) - Amrullah, Amrullah; Imaduddin, Imaduddin; Suryanti, Suryanti (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study aims to determine the influence or impact of workload, work discipline, and work environment on the performance of employees, particularly in the environment of the Organization Bureau of the Regional Secretariat of South Sulawesi Province. The approach used in this research is a quantitative approach with a simple linear analysis method. The population in this study consists of workers involved in the Organization Bureau of the Regional Secretariat of South Sulawesi Province, totaling 55 employees. Since the population size is less than 100, the study employs total sampling, making the entire population the sample. The results of the study indicate that workload and work environment have a positive and significant effect on employee performance, while work discipline has a positive but not significant effect. The analysis of the coefficient of determination shows a coefficient value of 48.80%. This indicates that 48.80% of the performance of employees in the Organization Bureau of the Regional Secretariat of South Sulawesi Province is influenced by the three independent variables, namely workload (X1), work discipline (X2), and work environment (X3), while the remaining 51.20% is influenced by other variables not observed in this study.